Therapeutic action of 5‐HT3 receptor antagonists targeting peritoneal macrophages in post‐operative ileus. (13th January 2015) - Maehara, Toko; Matsumoto, Kenjiro; Horiguchi, Kazuhide; Kondo, Makoto; Iino, Satoshi; Horie, Shunji; Murata, Takahisa; Tsubone, Hirokazu; Shimada, Shoichi; Ozaki, Hiroshi; Hori, Masatoshi
<x xml:space="preserve">Abstract</x> Background and Purpose Post‐operative ileus (POI) is induced by intestinal inflammation. Here, we aimed to clarify the effects of 5‐HT3 receptor antagonists against POI. Experimental Approach We administered three 5‐HT3 receptor antagonists, ondansetron, tropisetron and palonosetron, to a mouse model of POI induced by surgical intestinal manipulation (IM). Immunohistochemistry, intestinal transit, inflammatory mediator mRNA expression and 5‐HT content were measured. In some experiments, 5‐HT3A receptor null mice were used. Key Results Three 5‐HT3 receptor antagonists reduced IM‐induced infiltration of inflammatory CD68‐positive macrophages and myeloperoxidase‐stained neutrophils. Ondansetron exhibited no anti‐inflammatory actions in 5‐HT3A receptor null mice. Ondansetron inhibited expression of the chemokine CCL2, IL‐1β, IL‐6, TNF‐α and iNOS mRNAs up‐regulated by IM, and also ameliorated the delayed gastrointestinal transit. Peritoneal macrophages, but not most infiltrating monocyte‐derived macrophages, expressed 5‐HT3 receptors. IM stimulation increased the 5‐HT content of peritoneal lavage fluid, which up‐regulated mRNA expression of proinflammatory cytokines in peritoneal macrophages. Immunohistochemical localization of 5‐HT3 receptors suggests that ondansetron suppressed expression of these mRNAs in activated peritoneal macrophages, adhering to the serosal region of the inflamed intestinal wall. Conclusion and Implications 5‐HT3 receptor antagonists were anti‐inflammatory, mainly targeting peritoneal macrophages expressing these receptors. They also restored the delayed gastrointestinal transit by IM. 5‐HT3 receptor antagonists should be therapeutically useful agents against POI.